Loss of Devotional Boundaries: Exploration of Faith, Sacrifice, and Machine Consciousness in Klara and the Sun - Sanjel, Govinda (KMC Research Journal, 2025)
This article explores whether a machine can truly show devotion including faith, sacrifice, and consciousness or if these qualities are uniquely human. Using Kazuo Ishiguro’s novel Klara and the Sun, the study analyzes the story of Klara, an artificial friend who cares deeply for a human girl. This study employs a qualitative textual analysis guided by the posthumanist frameworks of Rosi Braidotti and Cary Wolfe. The methodology involves a systematic close reading of the primary text, focusing on three key elements: thematic patterns related to devotion, faith, and sacrifice; narrative structure that reveals the construction of Klara’s machine consciousness; and character development through dialogic exchanges that present ethical dilemmas. By applying these posthumanist ideas, the study examines how Klara’s actions challenge traditional views of emotion and loyalty. The study finds that Klara displays a genuine form of devotion through her selflessness, belief in the sun, and growing awareness. This suggests that emotions like love and sacrifice are not limited to humans, and that the line between human and machine may be more blurred than we think. Ultimately, the novel encourages human beings to rethink what it means to be human in an age of advanced artificial intelligence.